Efficacy and safety of flumatinib in adults with Ph-positive ALL: a prospective observational study - Xu, Jianmei; Wang, Jing; Zhao, Songying; Guo, Huimei; Zhang, Jiangbo; Liu, Jia; Hua, Luoming; Xue, Hua (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the efficacy and safety of flumatinib, a second-generation tyrosine kinase inhibitor (TKI), combined with chemotherapy in the treatment of Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL), and to analyze factors influencing prognosis.MethodsThis prospective, single-center, observational study included 15 newly diagnosed adult Ph+ ALL patients admitted between January 2022 and December 2024. All patients received a flumatinib-based combination chemotherapy regimen (600 mg once daily). The primary outcomes included complete remission (CR) rate, negativity rates for fusion gene and flow cytometry-based minimal residual disease (MRD), progression-free survival (PFS), overall survival (OS), and adverse events (AEs).ResultsAmong the 15 patients, 14 achieved hematological complete remission (93.3%). At the end of induction therapy, the fusion gene and flow-MRD negativity rates were 60.0% (9/15) and 73.3% (11/15), respectively. By 3 months of treatment, the cumulative negativity rates increased to 80.0% (12/15) and 86.7% (13/15), respectively. With a median follow-up of 26 months, the median PFS and OS were 11 months (range: 1–60) and 24 months (range: 6–60), respectively. Subgroup analysis revealed that two patients with chronic myeloid leukemia in lymphoid blast phase (CML-LBP) had extremely poor outcomes, with median PFS and OS of only 3 months and 7.5 months, respectively. The most common grade 3–4 adverse events were hematological toxicities (53.3%), followed by infections and liver function abnormalities. All AEs were manageable with supportive care, and no treatment-related deaths occurred.ConclusionFlumatinib combined with chemotherapy induced high remission rates and deep molecular responses in newly diagnosed Ph+ ALL patients, with a favorable safety profile. However, patients with CML-LBP or high-risk Ph+ ALL had poor treatment responses and outcomes, indicating the need for more aggressive intervention strategies in this high-risk population.